Tailoring of band gap, dielectric and antimicrobial properties of silver iodide nanoparticles through Cu doping. (January 2022) - Ahmad, Nafis; Alshehri, A.M.; Khan, Z.R.; Ahmad, Irfan; Hasan, P.M.Z.; Melaibari, Ammar A.; Shkir, Mohd
Abstract: This work reports facile chemical synthesis of Cu doped silver iodide (AgI) nanostructures with 0.0, 0.5, 1.0, 2.5 and 5.0 wt% concentrations. As grown nanostructures crystals structures were investigated, using X-ray diffraction and surface morphology of nanostructures were analyzed as a function of Cu doping concentration using scanning electron microscope (SEM). Impact of Cu doping on electronic structure of AgI nanostructures were examined using diffuse reflectance spectra and photoluminescence spectroscopy. The band gap of nanostructures were calculated to be between 2.74 and 2.87 eV and decreases systematically as Cu doping concentration increases. Dielectric studies and electrical conductivity of nanostructures were also investigated as a function of Cu doping concentrations. Dielectric constant shows the significant improvement as Cu doping concentration rise. Antimicrobial activity of Cu:AgI nanostructures were analyzed against various bacteria. Optimum antimicrobial activity was observed against Streptococcus pyogenes and Enterococcus faecalis .